Smart Cities and Tourism: A Paradiplomatic Approach Between Jakarta and Galicia - Rafi Ferdilianto; Bariq Akmal Malik; Christopher David Evans; Fira Najwah BSA; Nadira Refiana (Journal of Paradiplomacy and City Networks, 2023)
This study investigates the role of paradiplomacy in fostering enhanced cooperation between Jakarta, Indonesia, and Galicia, Spain, focusing on smart city initiatives and tourism development. Sub-state actors such as city, NGO and MNC nowadays have the rights to participate in the national agenda. In this area, Jakarta and Galicia both are a good example, in which those cities have multiple similarities in achieving their national agenda.  Jakarta is known as a capital city of Indonesia, who become the main area of national economy improvement. Also in the other hand, Jakarta applied a concept of smart city in order to maximize the potential of its own area. Jakarta has sucessfully applied the concept correctly, which it answered by the infrastructure sector Jakarta made MRT and LRT which one of the goals of the concept. Galicia is known as city who has huge potential in its tourism sector and, also the management of the sector is rather quite neat. this paper explores the potential for bilateral paradiplomatic engagement to promote economic and infrastructural development. The findings suggest that paradiplomacy not only serves as a vital instrument for urban development but also paves the way for sustainable and mutually beneficial international collaborations.